Self-training and self-education in the professional formation of a Ukrainian citizen - Олександр Притула (Філософія освіти)
Carrying out self-training and self-education in the process of professional development, a citizen of Ukraine should use methods and means of self-assessment of his beliefs, knowledge, actions, etc. In this process, the adequacy of the performed self-assessment, its constructive, psychologically positive and pragmatic nature is important. Every person from childhood should not only form a certain basic philosophical culture, which will help him to achieve better self-esteem, but also strive to constantly find a community of those interested in philosophy. This community of philosophical self-education will change during life, however, it should be constantly present in a person’s life – a community of people who are informally interested in the philosophical questions of their life. It is noted that the methods and technologies of self-training and self-education, which are formed during education and implemented to a greater extent in adult life, in particular, in the professional development of a Ukrainian citizen, play a special role in the education of civic qualities of an individual. Carrying out professional activity, a person should not only master professional skills, but also expand his worldview and value, civic potential. In the process of professional development, a citizen must learn the principles of self-training and self-education, which were formed by the entire history of Ukrainian culture development. It is emphasized that self-training as a phenomenon of individual existence is impossible without self-education, which is based on the worldview position of a person regarding the importance and necessity of updating one’s own cognitive competencies, in particular in the field of professional development. Skills and methods of self-education are usually formed during studies in school and student environments. Also, self-education is based on the achievements of Ukrainian culture and science, those psychological and pedagogical standards that have developed in our country and are the gained collective experience of the Ukrainian people.